MAGNITUDE AND DIRECTION OF INTERNAL MIGRATIONS IN SALIHLI - Mehmet Akif CEYLAN (Fırat University, 2019)
The purpose of this paper is to study the magnitude and direction of internal migrations that occurred in recent periods in Salihli using geographic methods. Up-to-date and official data relating to the places of settlement, as well as the civil registry for the year 2011 as obtained from Turkish Statistical Institute (TUIK), were used. Based on these data, total population of Salihli town is around 159.945. Around 106.104 people within this population live in the Salihli town, 10.737 in other towns of the Manisa province, and 44.548 in other 80 provinces in Turkey. In other words, 66.3% of the total population registered in Salihli live in Salihli itself, 6.7% in other towns of the Manisa province, and 27.9% in other provinces in Turkey. Of the population registered in Salihli but residing out of the town itself and Manisa live particularly in Izmir (23.952), as well as in Istanbul (5.100), Ankara, (1.944), Antalya (1.347), Mugla (1.231) and other provinces. Among these provinces, Izmir ranks the first with approximately 53.7%. The fact that Izmir is the third biggest city in Turkey and located in the same region near the town plays an important role in preference of the population of Salihli for migration. In terms of regions, the distribution of population migrating from Salihli is as follows respectively: Aegean Region (66.3%), Marmara Region (16.8%), Central Anatolia Region (6.8%), the Mediterranean Region (4.8%), Eastern Anatolia Region (2.3%), Black Sea Region (1.8%) and South Eastern Anatolia Region (1.2%). These figures show that 2/3 of the population of Salihli preferred the Aegean Region. On the other hand, The South Eastern Anatolia and Black Sea Regions are the least preferred geographical regions. On the other hand, Salihli is also a town that attracts migrations. As a matter of fact, there are 29.840 people registered in other 80 provinces but living in Salihli. In other words, 19.2% of the population living in the town are immigrants. Consequently, approximately 1/5 of the population living in Salihli today originates from other provinces. Major provinces from which the town attracts migrations are Diyarbakir (3.083), Usak (2.260), Izmir (1.628), Mus (1.539) and Batman (1.500) respectively. Regional distribution of the provinces that have highest rate of migration to Salihli is as follows: Eastern Anatolia Region (28,3%), Aegean Region (26.5%), South Eastern Anatolia Region (23.9%), Central Anatolia Region (9.9%), Black Sea Region (4.9%)